The archaeology of New Netherland : a world built on trade - Lukezic, Craig; McCarthy, John P. (John Patrick), 1956- (University Press of Florida, 2021)
This volume illuminates the influence of the Dutch empire in North America, assembling evidence from seventeenth-century settlements located in present-day New York, New Jersey, Connecticut, Pennsylvania, and Delaware.